Federated defense in the Middle East - Alterman, Jon B. 1964- (CSIS report, 2015)
"This study examines the potential for a 'federated defense' approach to U.S. action in the Middle East, the constraints to closer military cooperation in the region, and specific capability areas that would benefit from federated defense. Stabilizing the Middle East requires continued attention and investment from the United States and its global allies and partners. Federated defense involves building partner capabilities in a way that shares the burden of providing security in a more effective and efficient manner. Federated defense would, over time, create partner capabilities that augment and complement U.S. capabilities. Doing so requires identifying discrete areas of cooperation between the United States and its allies and partners that would leverage partner capabilities in pursuing common security objectives. A more clearly defined strategic approach would improve communication, more effectively distribute the financial burden, better leverage complementary capabilities, and institutionalize senior-level dialogue on strategic goals and priorities"--Publisher's web site